Short run macroeconomic factors affecting car sales in Proton / Zahariah Mohd Zain … [et al.] - Mohd Zain, Zahariah; Abd Rahim, Lina Nadia; Mohamed Thaheer, Ahmad Shazeer; Samsudin, Amira Natasha (Universiti Teknologi Mara Selangor, 2020)
Malaysia had committed to be an automotive-producing country through the establishment of Proton in the year 1983. Since then, Proton has been quite a significant contributor to the Malaysian economy. People are influenced to purchase cars due to a number of factors; and these factors are studied in this research. This paper aims to identify the relationship between the macroeconomic indicators and the sales volume of cars in Malaysia. In achieving the objective, the study used secondary data gathered from Internet search, journals, and government agencies, which were then analyzed using descriptive statistic, correlation analysis, and multiple regression statistic. The result of the study shows that inflation and unemployment contribute significantly to the volume of car sales for Proton. On the other hand, gross domestic product (GDP) and interest rate do not have significant impact on the sales volume. These findings will provide Proton with valuable insights about which factors are the most influential, so they could strategize accordingly.